Relationship Between Ventricular Asynchrony and QRS Duration in Patients with Left Ventricular Systolic Dysfunction - Akhteruzzamanm, M; Rahman, A; Rahman, MA; Amin, R; Miah, MNA; Khan, AR; Chowdhury, TA; Hossain, A; Kashem, MA (Bangladesh Journal of Medicine, 2013)
Bangladesh Journal of Medicine, Vol 23 No 2, 2012, Page 52-58 DOI: http://dx.doi.org/10.3329/bjmed.v23i2.14984